2012
DOI: 10.1021/cs3007473
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Ni Catalyst for Direct Synthesis of Primary Amines from Alcohols and Ammonia

Abstract: This paper reports the synthesis of primary amines from alcohols and NH3 by an Al2O3-supported Ni nanoparticle catalyst as the first example of heterogeneous and noble-metal-free catalytic system for this reaction without additional hydrogen sources under relatively mild conditions. Various aliphatic alcohols are tolerated, and turnover numbers were higher than those of Ru-based homogeneous catalysts. The catalyst was recoverable and was reused. The effects of the Ni oxidation states and the acid–base nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
177
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(185 citation statements)
references
References 35 publications
(50 reference statements)
6
177
1
1
Order By: Relevance
“…The effect of hydrogen is also tested, and as shown in Table 4 Entries 3, 6, 9 and 10 for Ni/Al 2 O 3 and Ni/C, the conversion increases from 71% to 87% and 87% to 92%, respectively, suggesting that hydrogen has positive, though slight effect on the reaction for both Ni/Al 2 O 3 and Ni/C. At the same temperature of 160˝C (Entries 1 and 9), Ni/C exhibits better activity than Ni/Al 2 O 3, indicating the support may affect the activity of nickel [13]. From Figure 2, Ni in the fresh Ni/Al 2 O 3 and Ni/C catalysts were 14 nm and 6 nm, respectively, in crystallite size based on the Scherrer equation.…”
Section: Ni/al 2 O 3 and Ni/c Systemsmentioning
confidence: 97%
See 2 more Smart Citations
“…The effect of hydrogen is also tested, and as shown in Table 4 Entries 3, 6, 9 and 10 for Ni/Al 2 O 3 and Ni/C, the conversion increases from 71% to 87% and 87% to 92%, respectively, suggesting that hydrogen has positive, though slight effect on the reaction for both Ni/Al 2 O 3 and Ni/C. At the same temperature of 160˝C (Entries 1 and 9), Ni/C exhibits better activity than Ni/Al 2 O 3, indicating the support may affect the activity of nickel [13]. From Figure 2, Ni in the fresh Ni/Al 2 O 3 and Ni/C catalysts were 14 nm and 6 nm, respectively, in crystallite size based on the Scherrer equation.…”
Section: Ni/al 2 O 3 and Ni/c Systemsmentioning
confidence: 97%
“…Moreover, the support is found to exert great influence to the activity of the catalyst [13,16,17]. Two supports Al 2 O 3 and active carbon were investigated in aqueous ammonia with the results shown in Table 4.…”
Section: Ni/al 2 O 3 and Ni/c Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shortest and highly atom-economic route towards biobased amines is the direct coupling of lignin-derived alcohols with ammonia, producing water as the only by-product. However, only a few homogeneous and heterogeneous catalytic methods are known to yield amines 30,31 or nitriles 32 Nature Catalysis directly and the efficiency of these is largely limited by the structure of the substrate. We have found that a versatile building block, nitrile 4, can be obtained through direct transformation of 1G with ammonia using commercially available Ni/ SiO 2 -Al 2 O 3 .…”
Section: Nature Catalysismentioning
confidence: 99%
“…Due to their importance, much effort has been devoted to developing various approaches for the synthesis of primary amines, such as the alkylation of halides with NH3 [5,6], the reduction of nitriles [7,8], hydrocyanation and reduction of alkenes [9], hydroamination of olefins [10,11], amination of alcohols [12][13][14], and the reductive amination of carbonyl compounds [15][16][17]. Among the methods, the reductive amination of carbonyl compounds with NH3 was the most attractive and practical way of producing primary amines both in industry and academic laboratories.…”
Section: Introductionmentioning
confidence: 99%